1999
DOI: 10.1034/j.1399-3003.1999.13f21.x
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated protein kinase regulates IL‐8 expression in human pulmonary vascular endothelial cells

Abstract: The aim of this study was to examine the role of p38 mitogen‐activated protein (MAP) kinase in interleukin (IL)‐8 expression in tumour necrosis factor (TNF)‐α‐ and IL‐1α‐stimulated human pulmonary vascular endothelial cells. To this end, the phosphorylation and activation of p38 MAP kinase and the effect of SB 203580, a specific inhibitor of p38 MAP kinase activity, on p38 MAP kinase activity and IL‐8 expression in TNF‐α‐ and IL‐1α‐stimulated human pulmonary vascular endothelial cells were examined. TNF‐α‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…In glomerular endothelial cells, we demonstrated that LPS-induced IL-6 and IL-8 production partially depends on p38MAPK. P38MAPK dependency for LPS-induced cytokine release has been shown for several other types of endothelial cells, including human umbilical vein,25 26 human dermal microvascular,27 28 human pulmonary artery29 and rat pulmonary microvascular30 endothelial cells. Our finding that LPS-induced cytokine production by glomerular endothelial cells was only moderately blocked upon p38MAPK inhibition may be due to involvement of other kinases and transcription factors, such as phosphoinositide 3 kinase (PI3K)30 31 and nuclear factor κB 30 32 33.…”
Section: Discussionmentioning
confidence: 88%
“…In glomerular endothelial cells, we demonstrated that LPS-induced IL-6 and IL-8 production partially depends on p38MAPK. P38MAPK dependency for LPS-induced cytokine release has been shown for several other types of endothelial cells, including human umbilical vein,25 26 human dermal microvascular,27 28 human pulmonary artery29 and rat pulmonary microvascular30 endothelial cells. Our finding that LPS-induced cytokine production by glomerular endothelial cells was only moderately blocked upon p38MAPK inhibition may be due to involvement of other kinases and transcription factors, such as phosphoinositide 3 kinase (PI3K)30 31 and nuclear factor κB 30 32 33.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, the central role of p38 MAP kinase-dependent signaling in LPS-stimulated endothelium has been highlighted in recent studies (Hashimoto et al, 2000; Hippenstiel et al, 2000; Kotlyarov et al, 1999). Since Pyk2 has been implicated in the regulation of MAP kinases (Della Rocca et al, 1997; Rocic et al, 2001), we examined the role of p38 MAP kinase and p44/42 MAP kinase downstream of Pyk2 in MCP-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…In human pulmonary vascular endothelial cells, p38 mitogen‐activated protein kinase also plays an important role in the TNF‐α‐ and IL‐1‐activated signaling pathway, which regulates interleukin‐8 expression. No evidence is available regarding its role in the cerebral vascular endothelium 23 …”
Section: Discussionmentioning
confidence: 99%